Effects of plant growth regulators on callus, shoot and root formation in fluted pumpkin (telfaira occidentalis) (2007)
Root and stem explants of fluted pumpkin were cultured in medium containing different types and concentrations of plant growth regulators (PGRs). The explants were observed for callus, root and shoot formation parameters after four months. Differences among explants, plant growth regulators and their interaction were not significant for number of roots per plantlet. Callus formation was higher in stem than root explants. Stem explants formed more callus in medium containing naphthalene acetic acid than that containing indole acetic acid while the trend was opposite with root explants. Root explants did not form shoots, leaves or nodes in any of the PGR regimes, while a concentration of 1.5 mg/l benzylaminopurine (BAP) induced the highest numbers of shoots, nodes and leaves per stem explant. There was no callus, shoot, node and leaf formation by both explants when cultured in medium without PGRs while root formation was minimal.